VIBRATION CHARACTERISTICS STUDY OF DIFFERENT PIPE LENGTH WITH DIFFERENT END CONDITIONS - Badardin, N.A. (Asian Research Publishing Network, 2020)
In the present work, a free vibration analysis of a straight pipe span with various lengths was investigated. Finite element models were prepared using ANSYS Workbench software to obtain the natural frequencies and mode shapes numerically and the results were compared with the analytical calculation. Two end pipe supports (fixed-fixed and fixed-supported) were adopted to investigate the natural frequencies and their corresponding mode shapes. From the analysis, it was found that the natural frequency calculated using numerical and analytical results for the straight pipe with different lengths were having a good agreement. The same pipe settings were repeated for different types of pipe materials. The effect of the pipe end conditions, the fluid contained in the pipe and the pipe materials on the modal characteristics were then further investigated. It was found with the increase of pipe length; the natural frequencies decrease. For all pipe materials, with and without fluid, fixed-fixed pipes have higher natural frequencies than fixed-supported pipes. In all cases, the results show that the natural frequencies with any fluid inside the pipe were lower than the case of pipe without fluid. To predict the natural frequency, a linear equation is formulated using regression analysis relating the connection between the pipe length and its natural frequency. It was found that that there is a correlation between the first natural frequency and the length of the pipe. The regression equation has the form of a power function and the coefficient of determination is R2 â¥ 0.8 for all cases. This vibration characteristics analysis is important as it is the basic analysis to other dynamic analyses such as response spectrum analysis or harmonic analysis. Â© 2020 Â©2006-2015 Asian Research Publishing Network (ARPN). All Rights Reserved.